Effect of Postharvest UV-C Irradiation on Phenolic Compound Content and Antioxidant Activity of Tomato Fruit During Storage - Chang-hong LIU; Lu-yun CAI; Xian-ying LU; Xiao-xu HAN; Tie-jin YING (Journal of Integrative Agriculture)
Mature-green tomato fruit (Solanum lycopersicum cv. Zhenfen 202) were exposed to different UV-C irradiation at 2, 4, 8, and 16 kJ m-2 and then stored under the dark at 14?C and 95% relative humidity (RH) for 35 d. Of these four doses, UV-C irradiation at 4 and 8 kJ m-2 significantly increased total phenolic contents in present tomato fruit by 21.2 and 20.2%, respectively. Furthermore, UV-C irradiation at 4 or 8 kJ m-2 promoted the accumulation of total flavonoids and increased the antioxidant activity. 2 or 16 kJ m-2 UV-C irradiation also enhanced antioxidant activity, but to a lesser extent. Seven phenolic compounds, viz., gallic acid, (+)-catechin, chlorogenic acid, cafferic acid, syringic acid, p-coumaric acid, and quercetin in tomato fruit were identified and quantified by HPLC. Gallic acid was the major phenolic compound in tomato fruit and significantly correlated with antioxidant activity. 4 or 8 kJ m-2 UV-C irradiation significantly increased the contents of gallic acid, chlorogenic acid, syringic acid, p-coumaric acid, and quercetin. The optimum dose of UV-C irradiation in terms of increased phenolic compound content and enhanced Antioxidant activity was determined to be 4 or 8 kJ m-2.